Influence of the Energy of the Electrostatic Field on the Rates of Enzymatic Processes in the Aquatic Environment - Neduva, Alexander Sh.; Nikiforova, Lidia O.; Nikiforov, Andrew Yu. (Novel Aspects on Chemistry and Biochemistry Vol. 2, 2023)
The purpose of the research was to determine the mechanism of activation of microbial communities as a result of exposure to a constant electrostatic field. The complex of studies carried out on Biosystems at different values of the field strength and the time spent by cells in the physical field proved that it is possible to obtain both the activation of biochemical processes and the inhibition of the rate of endogenous respiration. The studies were carried out at electrostatic field strengths from 4.0 to 20.0 kV /m and the time the cells were in the physical field from 3.0 to 30.0 seconds. Further, within 2 hours, changes in the medium were recorded in terms of the total volume (output) of the antibiotic concentration and the enzymatic activity of the biocenosis for the case of activation or inhibition observed in the aquatic environment. The processing of the suspension was carried out in an electrostatic unit, which was installed outside the bioreactor. Next, the mixture was again returned to the bioreactor, which made it possible to maintain continuous circulation of the suspension. In parallel, the control system worked, but without a block with an electrostatic field. It was determined that 50% recirculation allows to obtain an acceleration of the oxidation of the intracellular substrate up to 40%, depending on the cellular mycelium. Based on the experimental results obtained, it is proposed to use electrostatic fields to accelerate the second stage of antibiotic biosynthesis, as well as to optimize the processes of oxidation of organic compounds in bioreactors during the biochemical purification of water systems.